Youth Civic Participation in Sustainable Suburban Development: The Role of Digital Technology Among Young People in Manglayang - Meldi Rendra; Khilda Afifah; Estananto Estananto (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
The ideas of civic empowerment have transformed the discourse on sustainable suburban development, particularly through the active involvement of young people and the use of digital participatory media. This study, conducted in Manglayang, Bandung, employs an observational method using participatory action research to explore pathways toward the final evolutionary stage of sustainable development, focusing on rural agriculture and social, legal, and welfare citizenship. The research identifies key typologies of youth engagement in sustainable development, including social empowerment, entrepreneurship, and millennial agricultural movements, all facilitated by digital participatory media platforms. It also highlights a redefined notion of youth citizenship, emphasizing membership and participation in both civil and economic spheres through voluntary and profit-oriented activities. The findings reveal that this active, empowered form of citizenship, supported by digital participatory media, is a critical driver of modernization and sustainable economic development in Manglayang, Bandung.